The Implications of Parliamentary Interrogation in the Iraqi Constitution of 2005 (Comparative Study) - Al-Shajlawe, Mohammed (Indonesian Journal of Law and Justice, 2025)
This study examines the implications of parliamentary interrogation in the 2005 Iraqi Constitution, focusing on its constitutional and political effects. The research aims to analyze whether parliamentary interrogation serves as an effective oversight mechanism and how it impacts government accountability, particularly regarding political responsibility and confidence withdrawal. The study employs an analytical method, utilizing constitutional texts from Iraq, Jordan, and Kuwait, combined with a comparative approach to evaluate differences in parliamentary oversight mechanisms. The findings reveal that parliamentary interrogation plays a crucial role in maintaining a balance between legislative and executive powers. However, the study identifies weaknesses in the existing procedures, suggesting the need for constitutional reforms to enhance parliamentary effectiveness.